PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI BERBASIS GENDER DI DESA TAKKALASI KABUPATEN SIDRAP - Mandjarreki, Sakaruddin; Andi Muhammad Fadly, (Istiqra: jurnal hasil penelitian, 2023)
The presence of women presents a new perspective in implementing strategies for implementing the gender-based national independent community empowerment (PNPM) program. Therefore, the research aims to find out how gender-based strategies are in implementing the national independent community empowerment program (PNPM) in Takkalasi Village, Sidrap Regency, South Sulawesi Province. This research uses a qualitative method with a phenomenological approach. The resources in this research consist of primary data and secondary data. To maintain the consistency of the methodology of this research, data collection techniques were also used following the constructivist tradition starting from the observation, interview, and documentation stages. After the data is collected, the next step is to carry out data analysis by following the tradition of qualitative research the conclusion of this research is One form of implementing the strategy for implementing the National Independent Community Empowerment Program (PNPM) based on gender in Takkalasi Village, Sidrap Regency, starting from building gender awareness, organizing community training, ensuring access and space for participation, women's economic empowerment and finally building a culture of women's leadership